A dystonic syndrome associated with anti-basal ganglia antibodies. Issue 6 (14th May 2004) - Edwards, M J; Dale, R C; Church, A J; Giovannoni, G; Bhatia, K P
Abstract : Anti-basal ganglia antibodies (ABGA) have been associated with movement disorders (usually tics and chorea) and psychiatric disturbance in children. This report describes five adult and adolescent patients (one male, four females; mean age of onset, 16 years (range, 13–35)) who presented subacutely with a clinical syndrome dominated by dystonia and had ABGA binding to antigens of similar molecular weights to those seen in Sydenham's chorea. Three patients had a clear history of respiratory infection before the onset of their symptoms. Three patients received immunosuppressive treatment, with three showing a notable reduction in symptoms. It is hypothesised that dystonia in adults or adolescents may be part of the clinical spectrum of the post-infectious syndrome associated with ABGA.